First Experience: The Use of Spine Navigation at Arifin Achmad General Hospital, Riau Province: A Case Report - Wirdayanto, Ade; Lestari, Enny; Randa, Said Rafly Okta; Puteri, Sherly Aprilia Perel (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: Neuronavigation is a navigation system that assists neurosurgeons in performing surgery using real-time three-dimensional images from CT, MRI, or C-arm, providing benefits such as shortened operation duration, increased accuracy, and reduced radiation exposure for both patients and operators. In Indonesia, the use of neuronavigation in spine surgery is still rare, and no literature explains the experience of using this technology. Case Report: We reported the first experience of using neuronavigation at Arifin Achmad General Hospital, Riau Province, in a case of thoracic canal stenosis. A 53-year-old male patient, a palm oil farmer, presented with weakness in both lower limbs, urinary and fecal incontinence, and increased physiological reflexes. MRI examination revealed spinal cord stenosis at thoracic discs VII-X. The patient underwent decompressive laminectomy and posterior stabilization assisted by neuronavigation. The use of neuronavigation allowed precise and efficient placement of surgical instruments, dynamically displayed on the monitor screen, reducing radiation exposure and increasing the accuracy of pedicle screw placement. Conclusion: The use of navigation technology in spinal surgery will be an innovation that increases efficacy and patient safety. Its adoption is expected to become more common as more literature explains its benefits, especially in spinal surgery.